Knowledge sharing behaviour among non-academic staff in higher learning institutes: the role of trust and perceived risk - Rahman, Muhammad Sabbir; Mat Daud, Nuraihan; Raman, Murali (The University of Hong Kong, 2018)
The purpose of the paper is to analyse knowledge sharing behaviour among non-academic staff of higher learning institutions. This research focuses on the mediation impact of perceived risk on trust and knowledge sharing behaviour. The research also proposes actions that can be taken by higher learning institutions to enhance trust among the staff in order to create a knowledge sharing environment at the workplace. This research applied confirmatory factor analysis and Structural Equation Modeling (SEM) to evaluate the proposed measurement model and proved the research hypotheses. The findings from the research show that perceived risk plays a strong mediating role between trust and knowledge sharing behaviour among the non-academic staff of higher learning institutions. The SEM analysis also confirmed that the research model shows a good fit. This research highlights issues concerning knowledge sharing practices among non-academic staff and provides some recommendations to the managers to address these issues. The researchers agreed that more research needs to be done in this area as there are aspects that are yet to be explored. The findings of this research serve to add to the literature on knowledge sharing focussing on non-academic staff of higher learning institutions.